2013
DOI: 10.1523/jneurosci.1770-13.2013
|View full text |Cite
|
Sign up to set email alerts
|

Blood Oxygen Level-Dependent Activation of the Primary Visual Cortex Predicts Size Adaptation Illusion

Abstract: In natural scenes, objects rarely occur in isolation but appear within a spatiotemporal context. Here, we show that the perceived size of a stimulus is significantly affected by the context of the scene: brief previous presentation of larger or smaller adapting stimuli at the same region of space changes the perceived size of a test stimulus, with larger adapting stimuli causing the test to appear smaller than veridical and vice versa. In a human fMRI study, we measured the blood oxygen level-dependent activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
102
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(118 citation statements)
references
References 68 publications
14
102
2
Order By: Relevance
“…Consistent with our results, recent studies also demonstrated that the topography of V1 neural activity closely mirrored the perceived object size that was significantly affected by spatiotemporal contexts (e.g., physical distance or the size of visual adaptor), even when the retinal input remains unchanged (Pooresmaeili et al 2013;Sperandio et al 2012). In the study conducted by Sperandio et al (2012), they presented subjects with a constant light stimulus and manipulated the perceived size of the stimulus afterimage by varying the viewing distance of a back screen holding the afterimage.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with our results, recent studies also demonstrated that the topography of V1 neural activity closely mirrored the perceived object size that was significantly affected by spatiotemporal contexts (e.g., physical distance or the size of visual adaptor), even when the retinal input remains unchanged (Pooresmaeili et al 2013;Sperandio et al 2012). In the study conducted by Sperandio et al (2012), they presented subjects with a constant light stimulus and manipulated the perceived size of the stimulus afterimage by varying the viewing distance of a back screen holding the afterimage.…”
Section: Discussionsupporting
confidence: 92%
“…They found that the spatial distribution of V1 activity expanded to the more eccentric representation of the visual field as the perceived size of the afterimage increased with the viewing distance, suggesting neuronal populations in V1 encode the size information of the perceived rather than the physical visual input. In another study performed by Pooresmaeili et al (2013), using a visual adaptation paradigm, they found that the spatial extent of V1 activation closely resembled the perceived size of the testing stimulus that was altered by the size of adapting stimulus. Moreover, other recent studies also demonstrated that neural activity in V1 could encode other perceived stimulus properties (e.g., brightness and shape; Boyaci et al 2007;Michel et al 2013).…”
Section: Discussionmentioning
confidence: 89%
“…Finally, the perceived size of an afterimage or test stimulus, following an adaptor stimulus, has been shown to modify the BOLD response in V1. A larger perceived size corresponded to a stronger response in more eccentric regions (Sperandio et al, 2012), or a larger activated surface area (Pooresmaeili et al, 2013). The studies above suggest that V1 activation is modulated by feedback from higher cortical areas, possibly in the ventral visual stream.…”
Section: Saccade-and Illusion-related Activationmentioning
confidence: 79%
“…This view is supported by findings demonstrating that functional and anatomical features of V1 predict participants' susceptibility to visual illusions (Schwarzkopf & Rees, 2013;Schwarzkopf, Song, & Rees, 2011). In addition, local inhibitory mechanisms within V1 directly contribute to size rescaling when it is induced by size adaptation (Pooresmaeili et al, 2013). However, there is also evidence that higher visual areas modulate the encoding of perceived size in V1.…”
Section: Introductionmentioning
confidence: 82%
“…However, vision does not only integrate information across space but also over time, as indicated by another illusion-the size adaptation effect. There, a circle appears smaller when a larger "adaptor" circle precedes it and larger when it follows a smaller adaptor circle (e.g., Pooresmaeili, Arrighi, Biagi, & Morrone, 2013). Although both illusions rely on different types of information integration, both affect the perceived size of a target circle.…”
Section: Introductionmentioning
confidence: 99%